Битвы арабов и хазар за Дербент и Баланджар в первой половине VII в. - Калинина, Т.М. (Хазарский альманах, 2020)
The author of the article once again turns to the analysis of known information of Arab-Persian historians of the 9th–10th centuries AD about the actions of the troops of the Arab caliphate around Derbent and the Khazar city (or river) Balanjar in the early to middle of 7th century AD. Based on a critical analysis and comparison of these sources, the author joins the conclusion made before him and some other historians about the unreliability of a number of messages and the reason for this phenomenon. The chronology of events attributed to the middle of the 7th century AD. Mention of the Khazars and Türks is separately explained by insuffi cient knowledge of Arab writers аbоut these peoples.